Why CCE Still a Challenge? - FATIMA, ROOHI (THE PRIMARY TEACHER, 2015)
On 6 March, 2014, there was an article in the newspaper, The Times of India, titled, “CCE has improved scores, not teaching”. In this article, a conversation with the CBSE Chairperson Mr. Vineet Joshi has also been published; the conversation, concluded “Shift in teaching methodology still a challenge”. This article raised some questions such as: why teaching has not improved, even after so many efforts? Or, Why Continuous and Comprehensive Evaluation still a Challenge? Or, is the attitude of teachers played any role in it? The following article is an effort to find out the answers of these questions as well as to study the Attitude of Teachers of Government and Non-Government Schools towards Continuous and Comprehensive Evaluation.